Determining α-tocopherol in refined bleached and deodorized palm olein using fourier transform infrared spectroscopy - Che Man, Yakoob; Wanna, Ammawath; Mirghani, Mohamed Elwathig Saeed (Elsevier, 2005)
Fourier transform infrared (FTIR) spectroscopy was developed for the determination of a-tocopherol in refined bleached and deodorized (RBD) palm olein. The calibration and validation samples were prepared by spiking known amount of a-tocopherol to produce a wide range of a-tocopherol up to 2000 ppm. The method was based on the sodium chloride (NaCl) windows, and the transmission path was fixed at 50 lm at room temperature. The partial least squares (PLS) calibration models for predicting a-tocopherol were developed by using the FTIR spectral region at 3100–2750 cm1. The accuracy of the method was comparable to that of the high-performance liquid chromatography (HPLC), with coefficients of determination (R2) from calibration samples of 0.9922. The models were validated and the R2 of validation and the standard errors of prediction (SEP) computed. The standard deviation of difference for repeatability (SDDr) for the method was comparable to that for HPLC. With its speed and ease of data manipulation by the computer software, FTIR spectroscopy is advantageous as a simple and rapid quantitative determining analytical tool for a-tocopherol in RBD palm olein.